How can Pingo Doce private label increase its sales in the baby food category? - Lomba, Inês Teixeira Domingos Mendes (2021)
This Work Project focuses on the baby food category and its main objective is to identify opportunities and challenges that Pingo Doce should address to increase its sales and grow the baby food category in its stores in Portugal. After analysing secondary data, we conducted in-depth interviews which allowed us to develop hypotheses. Then, we assessed the hypotheses through instore observations. We concluded that one of the main challenges Pingo Doce brand is facing is not being recognized as a trusted brand in the category. Additionally, manufacturer brands in the category are constantly doing price promotions and a small differential in price between the manufacturer brand on promotion and Pingo Doce private label leads respondents to prefer manufacturer brands over private label. To mitigate these challenges, Pingo Doce should have as main target, in the baby food category, the group with more potential of purchasing private label products in the category: children with an older age (more than 2 years) and their mothers who are more willing to take risks (concerning their purchase decisions in the baby food category) and more keen on purchase private labels’ products. Moreover, Pingo Doce should continue launching high quality products such as the new ‘Bolsa de Fruta’ and potentially increase sales in stores.